“Eficiencia de extractos vegetales para el control de stemphylium solani causante de la mancha gris del tomate en Lamas” - Pezo Córdova, Alfredo (2006)
This research was carried out in " El Pacifico" farm, KiUoalpa sector, in Lamas district and provínce, San Martín's regíon, located in 06° 20' 15''south latitude, 75° 3Cr 5" west longítude and 814 m.a.s.l., wíth the aim of evaluate and compare the effect of vegeta.bles e:xtracts looking for control of Stemphylíum so!aní whích causes gray ieaf spot of tomate in experimental plot , using extracts vegetables · such as Lonchoc.arpus nioou, Averrhoa c.arambola, Jacaranda copaia and Chenopodíum ambrosíoídas, with doses of 20 aná 40ml/I of water; the applícation of the extracts were rnade at an íntervais of 1 O days per 4 times, beginníng at 22 days after traspJanting, the evaiuations were made in the middfe and upper part of the p!ant, it consisted to count ami to measure the spot caused by the · füngus, the statistical mode! used for this research was a randomized complete block design, with 4 b!ocks and 1 O treatments. The resuits showed that in the middle part of the plant the extraci of Jacaranda oopaía with 20ml/I of water hada hígh efficacy (82,4%) compared wíth the standard sample 1 in the upper part of the plant the extract of Lonchocarpus nícou with 20 and 40 mili of water showed higher efficacy (91 and 90,6%) than the standard sampie; in general ali the extracts used in this research had a anti-fungal effect